'Nones' Belonging: Sunday Assemblies, Cathedrals and Quakers. Issue 2 (1st December 2020) - Toombs, Ian; Grant, Rhiannon
Abstract : This research note reports on observations of the Sunday Assembly and places this movement in the wider context of 'secular spirituality': those who do not hold traditional religious beliefs but engage in spiritual or religiously shaped practices. In particular, we argue that the group identified in the sociology of religion as 'Nones', or people who identify as 'spiritual but not religious', commonly engage in spiritual practices and have spiritual aspirations. Observations of Sunday Assemblies are compared with the situation of the Religious Society of Friends (Quakers) and other church settings such as cathedral attendance to shed light on varied religious participation by 'Nones'. As such, it suggests that researchers investigating nones or non-theists may need to better understand the spiritual nature of their engagement.